Laser fragmentation of photocatalyst particles based on bismuth silicates - Svetlichnyi, Valerii A.; Belik, Yulia A.; Vodyankin, Andrei A.; Fakhrutdinova, Elena D.; Vodyankina, Olga V. (Proceedings of SPIE)
In this work we fragmented of an aqueous suspension of a micron and submicron BSO particles sample via laser ablation. Also we carried out a comparative analysis of structure, phase composition, morphology, physicochemical and functional properties of materials before and after fragmentation. The results show that laser fragmentation leads to the formation of a homogeneous phase composition and better integration of bismuth in the bismuth silicate structure, as well as to an increase of photocatalytic properties of BSO during selective excitation in comparison with the initial material.